Perspektif Kesejahteraan Tenagakerja Dengan Model Penetapan Upah Minimum Kabupaten Kota - Rachmad Abduh (Iuris Studia: Jurnal Kajian Hukum, 2022)
Wages as compensation for employees for the obligations that have been carried out always cause problems when determining drinking wages which are carried out every year. This happens because the government's policy in determining the minimum wage set through legislation is considered not to have achieved a decent life. This is also because a decent standard of living cannot be equated from one area to another. The relationship between workers and employers or employers can be seen from the wages earned by workers. Workers must be viewed as human beings, it is natural for workers to get fair rewards and protection, so drinking wages should be able to meet the living needs of workers and their families even though it is simple. This research is descriptive analytical with the approach used is normative juridical. The data collected is then processed and analyzed qualitatively, using an inductive method to draw a conclusion